Presenting an Interpretive Structural Model of Employees' Compensation System toward Administrative Integrity in the Public Sector - Hossein Imani (University of Tehran, 2020)
Objective:Administrative factors and especially those which are relevant to human resource management are considered as threatening factors of administrative integrity in Iran and employees' compensation system is one of them; so if there is no ideal employees' compensation system, they would probably commit corruption in order to reach their self-interests or confront economical problems. Accordingly, we are going to present a model of employees’ compensation system toward administrative integrity. Methods: This research is based on Interpretive Paradigm and Interpretive Structural Modelling (ISM). The research is an applied one and the way of extracting data is an interview. The statistical population of the research is experts of the administrative and recruitment organization and the method of sampling is Purposive sampling method. Results: compensation system of employees results in administrative integrity on condition that concludes seven components which are "internal controls", "justice procedures", "performance-based compensation", "legal procedures", "transparent procedures", "documentary procedures", and and "motivational compensation". Results show that four components of the model are embedded in the linkage cluster, concluding "internal controls", "documentary procedures", "transparent procedures" and "justice procedures". These components are dynamic; hence any change of them would affect all the system. Components which are embedded in Autonomous cluster conclude "legal procedures" and "performance-based compensation" which imply influence and direction power of them in the model. Also, the component "motivational compensation" is embedded independent cluster which means high dependency of this component in contrast with the other components of the model. Conclusion: The compensation system of employees toward administrative integrity should have transparent and documentary procedures and also give priority to justice. Likewise, the effectiveness of the compensation system of employees to develop administrative integrity depends on the existence of legal procedures and regulations, settlement of internal controls, motivational compensation and performance-based compensation.